2022
DOI: 10.3389/fmicb.2022.973278
|View full text |Cite
|
Sign up to set email alerts
|

Comparative transcriptome analysis of MDBK cells reveals that BoIFN-γ augmented host immune responses to bovine herpesvirus 1 infection

Abstract: Bovine herpesvirus 1 (BoHV-1) is an alphaherpesvirus that causes infectious bovine rhinotracheitis and infectious pustular vulvovaginitis in cattle. Ιnterferon-gamma (IFN-γ) is a pleiotropic cytokine with antiviral activity that modulates the innate and adaptive immune responses. In this study, we prepared high-purity bovine interferon gamma (BoIFN-γ) dimer protein using prokaryotic expression system and affinity chromatography. We subsequently investigated the effect of BoIFN-γ on BoHV-1 infection in Madin-Da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…IFN-γ is thought to play a crucial role in the anti-MDV immune response and can directly or indirectly resist MDV replication through the induction of nitric oxide [ 36 , 37 , 38 ]. The results of the study indicated that the expression of IFN-γ in the two lymphoid organs was upregulated by MDV infection, and the vv strain MDV/RB1B induced stronger IFN-γ transcriptional upregulation than MDV/CVI988 at 7, 14, and 21 dpi, which showed a trend similar to that reported by Bavananthasivam et al [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…IFN-γ is thought to play a crucial role in the anti-MDV immune response and can directly or indirectly resist MDV replication through the induction of nitric oxide [ 36 , 37 , 38 ]. The results of the study indicated that the expression of IFN-γ in the two lymphoid organs was upregulated by MDV infection, and the vv strain MDV/RB1B induced stronger IFN-γ transcriptional upregulation than MDV/CVI988 at 7, 14, and 21 dpi, which showed a trend similar to that reported by Bavananthasivam et al [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…To further evaluate the BoHV-1 ICS assay, 131 samples collected from dairy cows, including healthy and known BoHV-1-infected cows, were analysed using the BoHV-1 ICS and quantitative real-time PCR (qPCR) for BoHV-1 DNA in parallel. The qPCR assay was performed as previously described ( Jiang et al, 2022 ). The FI T /FI C for each sample as determined by the ICS assay was assessed using a fluorescence analyser.…”
Section: Methodsmentioning
confidence: 99%
“…For instance, transfection of the Madin-Darby Bovine Kidney (MDBK) cells (Madin and Darby 1958 ), adherent epithelial cells frequently used as a bovine in vitro model (e.g. Li et al 2018 ; Han et al 2021 ; Jiang et al 2022 ), is challenging due to low success rates (Osorio and Bionaz 2017 ). Moreover, a plasmid-based system has its limitations, including difficulties in efficiently transferring the plasmid into the nucleus (Nakamura et al 2019 ; de Oliveira et al 2019 ).…”
Section: Introductionmentioning
confidence: 99%